ANALISIS SINTAKSIS KALIMAT KOMPLEKS DALAM BAHASA ARAB KLASIK dan MODERN - Miko, Muhammad Imam Juyat; Sarif, Abdullah (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
The study aims to analyze complex sentence syntax in classical and modern Arabic. Using a descriptive-analytic approach, the study explores complex sentence structure, differences and similarities between classical and modern Arabic, as well as their implications in Arabic learning. Data is collected from classical texts such as the Qur'an and modern literature, then analyzed to identify the dominant syntax patterns. The results show that although there are variations in the use of complex sentence structures between classical and modern Arabic languages, there are fundamental similarities in the syntax rules that regulate complex phrase formation. This research is expected to contribute to the teaching of Arabic and enrich the understanding of the Arabic evolution over time.